PROBLEMATIKA PENGUPAHAN KARYAWAN TRAINING PADA GEPREK MASBOY BANDAR LAMPUNG PERSPEKTIF HUKUM EKONOMI ISLAM - M. Iqbal Riansyah Iqbal; Relit Nur Edi; Susi Nur Kholidah (IAIN BONE, 2026)
This research aims to analyze the problems of wages for training employees at Ayam Geprek Masboy MSME in Sukarame District, Bandar Lampung, and review them from the perspective of Islamic Economic Law and positive law in Indonesia. The training period is often used by business actors to provide sub-standard compensation without transparent contracts. The research method used is qualitative with descriptive-analytical field research. Primary data were obtained through observation and interviews with owners and employees, while secondary data included labor regulations and fiqh muamalah literature. The results showed that the wage practice at Ayam Geprek Masboy was carried out based on unspecified oral contracts, where the wages provided were below the City Minimum Wage (UMK) standards. This is not only a violation of Article 60 of Law No. 13 of 2003 concerning Labor, but also contradicts the principles of Islamic Economic Law because it contains elements of gharar (uncertainty) in the contract and ignores the value of justice ('adl). This research recommends the need for reconstruction of work contracts into written ones and adjustment of decent wages to realize worker welfare and business blessings.